Images of Asia : selections from "Asian action" - Nagaraj, Di. Ar.; Asian Cultural Forum on Development (Bangkok : Asian Cultural Forum on Development, 1991)
Collection of articles and stories from Asian action, newsletter of the Asian Cultural Forum on Development, published since 1976.
Keywords: Asia